Prevalence and correlates of psychotic experiences amongst children of depressed parents. (30th September 2016) - Bevan Jones, Rhys; Mars, Becky; Collishaw, Stephan; Potter, Robert; Thapar, Ajay; Craddock, Nick; Thapar, Anita; Zammit, Stanley
Abstract: Psychotic experiences in young people are substantially more common than psychotic disorders, and are associated with distress and functional impairment. Family history of depression as well as of schizophrenia increases risk for psychotic experiences, but the prevalence of such experiences and their clinical relevance in offspring of depressed parents is unknown. Our objectives were to explore i) the prevalence of psychotic experiences amongst offspring of parents with recurrent unipolar depression and ii) the relationship between psychotic experiences and other psychopathology. Data were drawn from the 'Early Prediction of Adolescent Depression' longitudinal study of high-risk offspring (aged 9–17 years at baseline) of 337 parents with recurrent depression. Three assessments were conducted over four years. Psychopathology was assessed using the Child and Adolescent Psychiatric Assessment. Seventy-eight percent of families (n=262) had complete data on psychotic experiences at each of the three time points. During the study, 8.4% (n=22; 95% CI 5.0%, 11.8%) of offspring reported psychotic experiences on at least one occasion, and these were associated with psychiatric disorder, specifically mood and disruptive disorders, and suicidal thoughts/behaviour. Psychotic experiences amongst offspring of depressed parents index a range of psychopathology. Further research is needed to examine their clinical significance and long-term consequences. Highlights: We examined psychotic experiences amongst offspring of depressed parents. 8.4% of offspring reported psychotic experiences during the study. Psychotic experiences were associated with psychiatric disorder and suicidal thoughts/behaviour. Clinicians should ask about psychotic experiences in young people to ensure appropriate assessment and treatment.